Alterações citogenéticas na doença periodontal - Brandão, Paulo de Tarso Jambeiro (2012)
Periodontal diseases, an important public health problem, have their origin in the bacterial colonization in the gingival epithelium induces tissue response to inflammation, which is accompanied by increased mitotic activity, providing an opportunity for the occurrence of damage to genetic material that it added to further damage, it may promote future neoplastic process. Objective:In this context, this study was carried out to evaluate the occurrence of cytogenetic damage and apoptosis in patients with and without periodontal disease using the micronucleus test in exfoliated cells of keratinized mucosa. Method: A sample with 72 individuals, who comprised three groups: Group I, consisting of 21 individuals with gingivitis, Group II, consisting of 24 subjects with periodontitis; control group composed of 27 individuals without periodontal disease. Full mouth clinical examination was performed to define the periodontal status, as well as collecting exfoliated cells from keratinized mucosa to test frequency of micronuclei. Results:A total of 123.301 cells were analyzed. There was no statistically significant difference in the occurrence of micronucleus (p> 0.1) between groups: gingivitis, periodontitis and control. The occurrence of apoptosis was significantly higher among subjects with periodontitis compared to subjects with gingivitis (p <0.05) and controls (p <0.025).Conclusions: The findings demonstrated that there was a statistically significant difference between groups regarding the occurrence of apoptosis, indicative of genotoxic effects induced by periodontal inflammation.